2017
DOI: 10.1080/02656736.2017.1388929
|View full text |Cite
|
Sign up to set email alerts
|

Application of microwave ablation in the emergent control of intraoperative life-threatening tumor hemorrhage during hepatic surgeries

Abstract: MWA may be a feasible, effective and simple strategy for the emergent control of intraoperative hepatic tumour bleeding. To the best of our knowledge, this study represents the first reported cases of this novel application of MWA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 16 publications
(17 reference statements)
0
15
0
Order By: Relevance
“…In an animal experimental study, Song et al showed that contrast-enhanced ultrasound-guided percutaneous microwave coagulation therapy significantly decreased blood loss in a rabbit model of active liver bleeding [5] . It has been successfully used intraoperatively to control hepatic bleeding [6 , 7] . Percutaneous microwave ablation use for control of hepatic bleeding from an arterial source has also been reported [8 , 9] .…”
Section: Discussionmentioning
confidence: 99%
“…In an animal experimental study, Song et al showed that contrast-enhanced ultrasound-guided percutaneous microwave coagulation therapy significantly decreased blood loss in a rabbit model of active liver bleeding [5] . It has been successfully used intraoperatively to control hepatic bleeding [6 , 7] . Percutaneous microwave ablation use for control of hepatic bleeding from an arterial source has also been reported [8 , 9] .…”
Section: Discussionmentioning
confidence: 99%
“…Microwave ablation has been reported to be an ideal instrument to control hemorrhage due to hepatic neoplasia or during hepatic surgery because of its unique mechanism of action that results in coagulative necrosis . In case 2, MWA was thought to be a good choice for minimizing the risk of spontaneous hemorrhage, which is a common complication of hepatic hemangiosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Microwave ablation is a minimally invasive therapeutic technique that has mainly been used for the treatment of active hemorrhage of the liver in cases of trauma or ruptured vascular tumors. 9,10,14 Some studies have shown that MWA is useful for controlling life-threatening hemorrhages even when active bleeding occurs in a large-diameter vessel. 9,10,15 Microwave ablation has also been used to treat hypertrophic rhinitis, allergic rhinitis, and epistaxis in China.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Microwave ablation (MWA) is a relatively new technique which has been used intraoperatively to achieve hemostasis at surgical margins in laparotomy. 9 Many studies have shown that MWA is safe and effective for the treatment of active hemorrhage of the liver 9 and hemorrhaging angiosarcoma, 10 minimizing intraoperative blood loss. In recent years, MWA has also been used to treat epistaxis, and it has shown a high success rate.…”
Section: Introductionmentioning
confidence: 99%